The role of maternal nutritional status and inflammatory markers on postnatal weight retention and infant growth from a cohort study in United Arab Emirates - Zein, Mona Hashem EP. Abbas (2020)
The United Arab Emirates (UAE) has experienced rapid economic growth that provoked a shift in diet and lifestyle factors which triggered a marked increase in the prevalence of overweight and obesity particularly among women during their reproductive years. Pregnancy is a vulnerable period for increased weight gain and systematic metabolic inflammation that can dictate fetal adaptations at the earliest stages of the life, with possible long-lasting effects on offspring. These perspectives geared the initiation of Mother and Infant Study Cohort (MISC) to address maternal nutrition, infant feeding practices and its associations with metabolic markers. The current study which stems from (MISC) cohort was conducted from December 2015 and ended in June 2016 in the Emirates of Sharjah, Dubai and Ajman of United Arab Emirates (UAE). A total of 256 healthy pregnant Arab women aged 19 to 40 years with singleton pregnancy were recruited during the third trimester of pregnancy. Participants were interviewed once during pregnancy, then at delivery, at two and 6 months postpartum in the primary health care clinics. The data collected for the mothers included socio-demographic characteristics, lifestyle, dietary intake, and anthropometry upon recruitment and during the postnatal visits while for infants, anthropometric measurements, and feeding practices. Further, blood and breast milk samples were collected at birth from the mothers and at 6 months postpartum for the mothers and the infants. These included fasting blood sugar (FBS), insulin, lipid profile as well as High Molecular Weight Human Adiponectin (HMW) ADPN; Tumor Necrosis Factor-alpha (TNF-α) Interleukin-6 (IL-6), and High Sensitivity C Reactive protein (hs-CRP). In addition to the breast milk profile of adiponectin and hs-CRP. Descriptive analysis revealed a marked prevalence of excessive gestational weight gain (GWG) (39.1%) among the participant mothers and was prominent among overweight and obese mothers (53.9% and 48.7%) respectively. Besides, their diet quality index score was less than the optimum. At 6 months, multiple linear regression (MLR) revealed that postpartum weight retention (PPWR) decreased with increasing pre pregnancy body mass index (BMI) (β=-.43, p<0.01) and increased with increasing gestational weight gain (GWG) (β=.391, p<0.001), while serum FBS was the only metabolite parameter associated with retaining weight (β= 0.113, p<0.05). The maternal serum demonstrated significantly (p<0.01) elevated inflammatory cytokines and insulin among overweight/obese women compared to leaner mothers. At 6 months of infants’ age, examining the Z score growth parameters, no significant changes (p>0.05) have been encountered among the different feeding practices (exclusive, predominant breast feeding or mixed feeding (MF)). The serum insulin of the (MF) infants significantly exceeded 3 times (9.60 μIU/ml), the recorded levels in other feeding practices (p< 0.05). MLR models showed that as infants’ serum BG increased, lower infant body weight was predicted (β=-0.024, p=0.044). Infant birth BAZ and maternal serum adiponectin were positive predictors for the 6 months BAZ score (β=0.336, p=0.05) and (β=.241, p<0.05) respectively. In conclusion, excessive maternal weight represented in high pre-pregnancy BMI, excessive GWG and PPWR was the common denominator for the major study outcomes. These considered potentially modifiable risk factors which warrants developing culturally specific legislation to lessen the transgenerational impact of obesity. Though breastfeeding beneficial effects on infants’ weight fades after cofounder adjustments, nevertheless, promoting breastfeeding is a proactive endeavour that may contribute to infants’ metabolic programming against obesity in the long run.